Pengaruh Budaya Organisasi, Pengembangan Karir dan Kepuasan Kerja Terhadap Peningkatan Kinerja Aparatur Sipil Negara (ASN) di Sekretariat Daerah - Moha, Yulinda Agnesari (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2024)
This study aims to determine the effect of Organizational Culture, Career Development and Job Satisfaction Performance Improvement Against the State Civil Apparatus (ASN) in the Regional Secretariat of Gorontalo Province. The population in this study is the State Civil Apparatus (ASN) Regional Secretariat Gorontalo province. The study included overall ASN totaling 80 people as research subjects. Improved performance of data obtained through the test work, while data on organizational culture, career development and job satisfaction were collected through a questionnaire. These results indicate that: (1) The organizational culture affect the performance Apparatus, (2) career development affect the performance Apparatus, (3) job satisfaction affect the performance Apparatus and (4) Cultural organizations, career development, and job satisfaction simultaneously performance improvements affect the Apparatus. Based on these findings it can be concluded that, organizational culture, career development and job satisfaction gave a significant impact on performance improvement ASN.